Bioassay of conidial thermotolerance of Beauveria bassiana strains from different hosts and geographic origins - LI Hong-wen; FENG Ming-guang (浙江大学学报. 农业与生命科学版)
In order to search for fungal biocontrol agents adaptable to pest control during hot summer of southern China, aerial conidia of 12 Beauveria bassiana strains from different host insects and geographic origins were separately suspended in a solution containing 2% sucrose and 0.5% peptone. For each strain, the conidial suspension of 1 mL in a 10 mL glass tube was exposed to the thermal stress of 48 ℃in water bath. The residual viability of the conidia after a given period of exposure was measured as survival index, which was defined as the ratio of their germination rate (observed after 24 h incubation at 25 ℃) over the germination rate of unexposed conidia (blank control). Observations made at 6 min intervals during the thermal stress fitted well to a logistic equation (r2>0.98), which yielded the estimates of median lethal time (LT50) depicting fungal thermotolerance. As a result, the LT50 estimates fell in a range of 6.7-21.2 min, being significantly different among the 12 strains tested. The method developed is simple and convenient for the evaluation of conidial thermotolerance, and could be useful for screening of thermotolerable fungal biocontrol agents and enhancement of their field persistence.